(untitled) (European Journal of Marketing and Economics, 2020)
Under the restricted measures due to the global pandemic Covid-19, like all other services, financial services had difficulties in performing their financial activities. These difficulties are stronger at countries where financial services are denied for a long time. Financial services denial is an issue that has affected not only Albania but small Balkan countries as well. The reasons for this denial are many, but among them we can distinguish the lack of credit experience, as one of the common reasons to be excluded in these countries from the development of the financial sector. Currently, one of the reasons for the financial denial is the emergency created by Covid-19, where physical distancing and other measures taken by governments to restrict movement and services make financial service impossible. Thus, one of the most effective ways to perform financial services remotely is financial technology. Financial technology refers to the possibilities of financial innovation through technology that can result in new business models, applications, processes, or products with an effectiveness related to financial markets and institutions and the provision of financial services. This paper aims to present the challenges of the legal framework and regulatory institutions, to provide recommendations for its improvement, to enable the development of financial technology in the financial market in Albania. The paper address issues such as the Bank of Albania’s consideration on the Directive (EU) 2015/2366 On Payment Services (PSD II). What benefits or challenges would its implementation bring? How is the financial industry projected after the implementation of PSD II? What are the biggest job challenges with payment institutions that have not been to the market before or that bring technology innovations? The paper addresses the issue of money laundering through online digital transactions as well.